2008
DOI: 10.1042/bj20080078
|View full text |Cite
|
Sign up to set email alerts
|

Catalytically inactive phospholipase A2 homologue binds to vascular endothelial growth factor receptor-2 via a C-terminal loop region

Abstract: VEGF (vascular endothelial growth factor) regulates neovascularization through binding to its receptor KDR (kinase insert domain-containing receptor; VEGF receptor-2). We recently identified a catalytically inactive PLA(2) (phospholipase A(2)) homologue (KDR-bp) in the venom of eastern cottonmouth (Agkistrodon piscivorus piscivorus) as a third KDR-binding protein, in addition to VEGF(165) and tissue inhibitor of metalloproteinase-3. KDR-bp binds to the extracellular domain of KDR with a K(d) of 10(-8) M, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 30 publications
1
26
0
2
Order By: Relevance
“…The recent finding of strong and specific binding of Lys49 PLA 2 s to the VEGF receptor is intriguing, but the possible significance of this interaction in myotoxicity is unkown [40]. It is noteworthy, however, that binding of Lys49 PLA 2 s to this receptor occurs through the C-terminal region, known to play a key role in plasma membrane perturbation [41]. It has been observed that negatively-charged lipids in the plasma membrane may play a role in the binding of some locally-acting myotoxic PLA 2 s [42].…”
Section: Cell Bindingmentioning
confidence: 95%
“…The recent finding of strong and specific binding of Lys49 PLA 2 s to the VEGF receptor is intriguing, but the possible significance of this interaction in myotoxicity is unkown [40]. It is noteworthy, however, that binding of Lys49 PLA 2 s to this receptor occurs through the C-terminal region, known to play a key role in plasma membrane perturbation [41]. It has been observed that negatively-charged lipids in the plasma membrane may play a role in the binding of some locally-acting myotoxic PLA 2 s [42].…”
Section: Cell Bindingmentioning
confidence: 95%
“…We were able to find, isolate and characterize a new type of VEGF, named vammin, from the venom of V. ammodytes ammodytes, and VR-1 from the venom of D. russelli russelli (formerly Vipera russelli russelli) (Yamazaki et al, 2003) and several other snake venoms (Yamazaki et al, 2010). From the initial inspiration from the paper of HF (Komori et al, 1999), we got many interesting results (Fujiwara et al, 2008;Matsunaga et al, 2009;Suto et al, 2005;Tokunaga et al, 2005Tokunaga et al, , 2006Yamazaki et al, 2003Yamazaki et al, , 2005a2010;Yamazaki and Morita, 2006) and enjoyed our work on snake venom-derived VEGFs as a new subject with my colleagues and graduate students. …”
Section: A Growth Industrydexpanded Studies Of Vegfmentioning
confidence: 97%
“…Even less is known on the cell binding step of myotoxic PLA2 s, which is clearly essential for the display of their toxicity [14]. Receptors for myotoxins isolated from the venom of Oxyuranus scutellatus have been identified [15,16] and it has been suggested that the receptor of the Lys49 myotoxin is the VEGF (vascular endothelial growth factor) receptor itself [17,18]. The presence of specific plasma membrane receptors is also supported by the selectivity of some myotoxins for type I muscle fibers [19,20].…”
Section: Introductionmentioning
confidence: 99%